A model predictive current controlled bidirectional three-level DC/DC converter for hybrid energy storage system in DC microgrids - Zhang, Xinan (2020)
This letter proposes a new three-level dc/dc converter configuration for a hybrid energy storage system (HESS) in dc microgrids. It effectively integrates different energy storage devices (ESDs), such as battery and ultracapacitor (UC), using one converter with bidirectional power flow. Furthermore, the proposed converter provides the flexibility of independent regulation of different ESDs with significantly reduced inductor current ripple due to the availability of three voltage levels. The voltage ratings of power semiconductors employed in this converter are also reduced. To further enhance the performance of HESS, a constant switching frequency based model predictive current control is employed for HESS regulation. The design guideline and operating principle of the proposed converter are discussed. Experimental results are presented to verify the efficacy of the proposed converter and control.